A UML Reuse Framework and Tool for Requirements Engineering - Batista, Vitor A. (2013)
Requirement Engineering (RE) activities are critical by nature and mostly manual. Some automated support for tasks helps requirements engineers to reduce manual labor and, consequently, reduce defects rates and increase reuse and motivation. In this paper, we introduce a UML framework and tool support which automates part of the RE process. Using UML stereotypes as the core of this solution, we created a set of integrated tools composed by: (1) a reusable framework that models RE behavior patterns that are typically present in information system projects; (2) a function that allows the reuse of information provided by entity modeling; (3) a tool that automates the generation of application prototypes; (4) a tool for counting IFPUG Function Points; and (5)a tool that analyzes specific types of defects. Our findings indicate that the framework and the automated support are effective at RE modeling and review.  In addition, they increase motivation and promote team engagement, through elimination of repetitive activities.